1992
DOI: 10.1111/tri.1992.5.s1.40
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre trial of ABO-incompatible kidney transplantation

Abstract: A multicentre study of ABO incompatible kidney transplantation using Biosynsorb was started in Japan in November 1989. A total of 51 cases were registered comprising 23 cases of A incompatibility, 26 cases of B incompatibility and two cases of AB incompatibility. The .removal of antibodies (IgG and lgM) was carried out using Biosynsorb in 16 cases, plasmapheresis in four cases and use of both combined in 31 cases. The treatment using Biosynsorb was repeated 3.4 times on average. Serum titres of anti-A (IgG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In Japan up to three sessions of plasmapheresis after ABO‐incompatible kidney transplantation are covered by National Health Insurance. The results in the 51 patients who underwent transplantation after antibody removal by immunoadsorption with Biosynsorb ® have been reported previously (12).…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…In Japan up to three sessions of plasmapheresis after ABO‐incompatible kidney transplantation are covered by National Health Insurance. The results in the 51 patients who underwent transplantation after antibody removal by immunoadsorption with Biosynsorb ® have been reported previously (12).…”
Section: Methodsmentioning
confidence: 73%
“…Immunoadsorption with Biosynsorb ® (Unicom Corporation, Tokyo, Japan) was carried out in 51 of 441 patients (2,3,6,10–12). Subsequently, production of Biosynsorb ® was discontinued, and only plasmapheresis was used to remove antibodies before transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…In our reported case, the preoperative depletion of natural antibody and splenectomy were intentionally avoided. Ota et al [9] reported the results of 51 cases and recommended a reduction of antibody titers below 16 at the time of transplantation for a successful outcome. Although this patient showed a high titer of natural antibody against B antigen before transplantation, the titer dropped just after transplantation and maintained at low level thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the anti-A or anti-B antibodies of the recipients by plasmapheresis or immunoadsorption has become an essential treatment for kidney transplantation across the ABO barrier [2-41. As a result, graft and patient survival are nearly equal to those of ABOcompatible transplantation [9]. However, discussions have been focused on only the anti-A or anti-B antibody titer of the recipient, and quantitative evaluation of ABO antigens in the kidney tissue of the donor has been neglected.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, we have been making continuous efforts in ABO-incompatible kidney transplantation since 1989 to expand the opportunities for living kidney transplantation in Japan [1][2][3][4][5][6]. The Japanese ABO-incompatible kidney transplantation committee had started the registry since 1997 [5,6].…”
Section: Introductionmentioning
confidence: 99%